Outcomes and Challenges of A PD-First Program, A South-African Perspective. Issue 3 (May 2018) - Davidson, Bianca; Crombie, Kenneth; Manning, Kathryn; Rayner, Brian; Wearne, Nicola
Background: South Africa (SA) currently performs the most peritoneal dialysis (PD) in Africa. Yet outcome data on PD programs on the continent are limited. With the escalating need for renal replacement, PD remains a life-saving modality especially as hemodialysis is limited in the public sector. This study aims to evaluate and report the outcomes of a PD-First program performed in a resource-limited setting and identify factors linked to poor outcomes. Methods: This observational cohort study was performed at Groote Schuur Hospital, analyzing all PD patients retrospectively from January 2008 to June 2014 and thereafter prospectively until June 2015. Variables included demographics, adequacy, modality, fluid status, cardiovascular disease, and diabetes. The influence of these variables on peritonitis rate, technique survival, and patient survival was assessed. Results: In total, 230 patients were initiated on PD, 31 of whom excluded as they were on PD for < 90 days. The mean age was 39.7 ± 10.4 years (standard deviation [SD]), 49.8% were male, 63.8% were mixed ancestry and 9.8 % were diabetic at dialysis initiation. The average length of time on PD was 17 months (interquartile range [IQR] 8 – 32). The peritonitis rate was 0.87 (confidence interval [CI] 7.8 – 9.7) events per patient year. The 1-, 2- and 5-year patient and technique survival was 91.3%, 79.6%, 50.2% and 85.0%, 75.2%, 45.0%, respectively. Diabetes subdistribution hazard ratio (SHR) 3.16 (95% CI 1.34 – 7.45, p = 0.009) strongly predicted an increased cumulative incidence for death when accounting for competing risks. African ethnicity SHR 2.16 (95% CI 1.26 – 3.71, p = 0.005) was a strong predictor of increased cumulative incidence for technique failure. Conclusions: In our PD-First program the results are encouraging, despite the lack of home visits due to safety, resource limitations, and a high disease burden. Technique failure in the African race needs further evaluation. Peritoneal dialysis remains a viable, life-saving alternative in an African setting.